Endosomal H2O2 Molecules Act as Signaling Mediators in Akt/PKB Activation - Sujin Park; Chaewon Kim; Sukyeong Heo; Dongmin Kang (Antioxidants)
Receptor-mediated endocytosis (RME) is a commonly recognized receptor internalization process of receptor degradation or recycling. However, recent studies have supported that RME is closely related to signal propagation and amplification from the plasma membrane to the cytosol. Few studies have elucidated the role of H2O2, a mild oxidant among reactive oxygen species (ROS) in RME and second messenger of signal propagation. In the present study, we investigated the regulatory function of H2O2 in early endosomes during signaling throughout receptor-mediated endocytosis. In mammalian cells with a physiological amount of H2O2 generated during epidermal growth factor (EGF) activation, fluorescence imaging showed that the levels of two activating phosphorylations on Ser473 and Thr308 of Akt were transiently increased in the plasma membrane, but the predominant p-Akt on Ser473 appeared in early endosomes. To examine the role of endosomal H2O2 molecules as signaling mediators of Akt activation in endosomes, we modulated endosomal H2O2 through the ectopic expression of an endosomal-targeting catalase (Cat-Endo). The forced removal of endosomal H2O2 inhibited the Akt phosphorylation on Ser473 but not on Thr308. The levels of mSIN and rictor, two components of mTORC2 that work as a kinase in Akt phosphorylation on Ser473, were also selectively diminished in the early endosomes of Cat-Endo-expressing cells. We also observed a decrease in the endosomal level of the adaptor protein containing the PH domain, the PTB domain, and the Leucine zipper motif 1 (APPL1) protein, which is an effector of Rab5 and key player in the assembly of signaling complexes regulating the Akt pathway in Cat-Endo-expressing cells compared with those in normal cells. Therefore, the H2O2-dependent recruitment of the APPL1 adaptor protein into endosomes was required for full Akt activation. We proposed that endosomal H2O2 is a promoter of Akt signaling.